1992
DOI: 10.1002/bjs.1800790730
|View full text |Cite
|
Sign up to set email alerts
|

Flush aortic tie versus selective preservation of the ascending left colic artery in low anterior resection for rectal carcinoma

Abstract: The effects of two methods of colonic vascular ligation were studied in 143 consecutive patients who underwent low anterior resection with total mesorectal excision and full mobilization of the splenic flexure. Either the ascending left colic artery (ALCA) was selectively preserved (n = 52) or a flush aortic ligation was performed (n = 91). In those with a protective colostomy, the radiological leak rate was 12 per cent when the ALCA was preserved (n = 41) and 10 per cent when a flush aortic tie was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 6 publications
1
47
1
2
Order By: Relevance
“…Ligation distal to the first branch of the inferior mesenteric artery ensures a viable blood supply to the bowel from which the stoma will be created. Corder et al studied 143 consecutive patients but failed to show any association between the method of vascular ligation and the risk of tumor recurrence and death [6]. Furthermore, anastomotic leak rates were not related to the method of vascular ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligation distal to the first branch of the inferior mesenteric artery ensures a viable blood supply to the bowel from which the stoma will be created. Corder et al studied 143 consecutive patients but failed to show any association between the method of vascular ligation and the risk of tumor recurrence and death [6]. Furthermore, anastomotic leak rates were not related to the method of vascular ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic lymph nodes follow the arterial supply, thus high ligation can remove the highest draining nodes that may harbor occult microscopic metastases. Enker et al adhered to this principle strictly and reported 5-year disease-free survival rates of up to 70 % in stage III [6].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dworkin et al [11] and Seike et al [12] used Doppler flowmetry to demonstrate that IMA clamping resulted in a >50% blood-flow reduction to the anastomosis, and a randomised controlled trial by Tocchi et al [23] reported that anastomotic leakages were significantly more frequent following HL of the IMA for diverticular disease in the left colonthan the preservation of the IMA and the LCA. Corder et al [24] and Hall et al [25] reported that HL of the IMA does not affect anastomotic leakage rates in the context of oncologic surgeries, while Kobayashi et al [19] and Sekimoto et al [20] demonstrated that operative results were not significantly different when comparing HL of the IMA and the preservation of the IMA and the LCA during laparoscopic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of ligating the inferior mesenteric artery flush with the aorta may at times facilitate the lowering of the left colon and the performance of a sphincter-saving procedure, but it has failed repeatedly [25, 31, 32]to improve survival regardless of the stage of the disease [33]and to reduce the LR rate. The results suggest that metastatic involvement of lymph nodes at a level near the aorta indicates that further proximal spread may have already occurred [22].…”
Section: The Operationmentioning
confidence: 99%